2016
DOI: 10.1155/2016/2534037
|View full text |Cite
|
Sign up to set email alerts
|

Sampson’s Artery Hemorrhage after Inguinal Hernia Repair: Second Case Reported

Abstract: Sampson artery is normally obliterated in postembryonic development. In rare cases it can remain patent and complicate a routine outpatient herniorrhaphy when severed. This is the second reported case in the available English literature of hemoperitoneum due to bleeding from a patent Sampson's artery following an open inguinal hernia repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In this case, we present a patient who had an open inguinal hernia mesh repair using the Lichtenstein technique, complicated by postoperative intraperitoneal hemorrhage requiring reoperation. A literature review reveals only two confirmed previous cases [ 4 , 5 ]. While a third case has alluded to this particular complication, it has been disregarded by previous scholarly journals as “confirmed [ 6 ].” Bleeding, similar to the previous cases [ 4 , 5 ], was found to originate from the artery of Sampson, a vessel which is normally obliterated in postembryonic development but which can persist as a branch of the uterine artery that runs along the length of the uterine round ligament in adult females.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…In this case, we present a patient who had an open inguinal hernia mesh repair using the Lichtenstein technique, complicated by postoperative intraperitoneal hemorrhage requiring reoperation. A literature review reveals only two confirmed previous cases [ 4 , 5 ]. While a third case has alluded to this particular complication, it has been disregarded by previous scholarly journals as “confirmed [ 6 ].” Bleeding, similar to the previous cases [ 4 , 5 ], was found to originate from the artery of Sampson, a vessel which is normally obliterated in postembryonic development but which can persist as a branch of the uterine artery that runs along the length of the uterine round ligament in adult females.…”
Section: Introductionmentioning
confidence: 78%
“…In this case, we present a patient who had an open inguinal hernia mesh repair using the Lichtenstein technique, complicated by postoperative intraperitoneal hemorrhage requiring reoperation. A literature review reveals only two confirmed previous cases [4, 5]. While a third case has alluded to this particular complication, it has been disregarded by previous scholarly journals as “confirmed [6].…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic TAPP repair treatment of hernias has demonstrated several benefits when compared to the conventional surgery approach. These benefits include more optimal cosmesis, less postoperative pain, and faster resumption of physical, professional, and sports activities [ 2 , 3 ]. The preperitoneal space is largely avascular and is composed of adipose tissue, loose connective tissue, and membranous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…ligament with damage to Sampson's artery following an inguinal hernia repair. In these two cases, the bleeding from Sampson's artery necessitated a return to the operating room with evacuation of 1 liter of hemoperitoneum [1,2]. While general surgeons rarely handle Sampson's artery, they ideally should be familiar with the vessel given the serious sequela associated with an unrecognized injury to Sampson's artery.…”
Section: Sampson's Arterymentioning
confidence: 99%